Microbial flora, probiotics, Bacillus subtilis and the search for a long and healthy human longevity - Facundo Rodriguez Ayala; Carlos Bauman; Sebastián Cogliati; Cecilia Leñini; Marco Bartolini; Roberto Grau (Microbial Cell)
Probiotics are live microorganisms that have beneficial effects on host health, including extended lifespan, when they are administered or present in adequate quantities. However, the mechanisms by which probiotics stimulate host longevity remain unclear and very poorly understood. In a recent study (Nat. Commun. 8, 14332 (2017) doi: 10.1038/ncomms14332), we used the spore-forming probiotic bacterium Bacillus subtilis and the model organism Caenorhabditis elegans to study the mechanism by which a probiotic bacterium affects host longevity. We found that biofilm-proficient B. subtilis colonized the C. elegans gut and extended the worm lifespan significantly longer than did biofilm-deficient isogenic strains. In addition to biofilm proficiency, the quorum-sensing pentapeptide CSF and nitric oxide (NO) represent the entire B. subtilis repertoire responsible for the extended longevity of C. elegans. B. subtilis grown under biofilm-supporting conditions synthesized higher levels of NO and CSF than under planktonic growth conditions, emphasizing the key role of the biofilm in slowing host aging. Significantly, the prolongevity effect of B. subtilis was primarily due to a downregulation of the insulin-like signaling system that precisely is a key partaker in the healthy longevity of human centenarians. These findings open the possibility to test if the regular consumption of B. subtilis incorporated in foods and beverages could significantly extend human life expectancy and contribute to stop the development of age-related diseases.